2015
DOI: 10.1103/physrevb.91.184504
|View full text |Cite
|
Sign up to set email alerts
|

Counterflow quantum turbulence of He-II in a square channel: Numerical analysis with nonuniform flows of the normal fluid

Abstract: We perform a numerical analysis of counterflow quantum turbulence of superfluid 4 He with nonuniform flows by using the vortex filament model. In recent visualization experiments nonuniform laminar flows of the normal fluid, namely, Hagen-Poiseuille flow and tail-flattened flow, have been observed. Tail-flattened flow is a novel laminar flow in which the outer part of the Hagen-Poiseuille flow becomes flat. In our simulation, the velocity field of the normal fluid is prescribed to be two nonuniform profiles. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 27 publications
8
39
0
Order By: Relevance
“…The studies [75,78,80] reviewed above confirmed the steady state condition Eq. (32) of Vinen's equation:…”
Section: Comparison Of γ In Vinen's Equationsupporting
confidence: 54%
See 3 more Smart Citations
“…The studies [75,78,80] reviewed above confirmed the steady state condition Eq. (32) of Vinen's equation:…”
Section: Comparison Of γ In Vinen's Equationsupporting
confidence: 54%
“…Yui and Tsubota studied counterflow quantum turbulence in a duct by performing numerical simulations [77,78]. The visualization experiment of thermal counterflow by Marakov et al showed that the normal fluid velocity distribution becomes a Poiseuille profile, a tail-flattened profile, and a turbulent profile [35], as explained above.…”
Section: Poiseuille and Tail-flattened Normal Flow In A Ductmentioning
confidence: 99%
See 2 more Smart Citations
“…The shapes and dynamics of bare vortices with fixed boundary conditions can, in principle, be calculated using the BiotSavart law [30][31][32][33]. However, the implementation of this approach is not straightforward due to the additional acquired mass of the dopant atoms and a possible vorticity-dependence of the droplet shape.…”
Section: Main Textmentioning
confidence: 99%